Reaction Times When Switching From Autonomous to Manual Driving Control: A Pilot Investigation. (September 2016) - Funkhouser, Kelly; Drews, Frank
As autonomous vehicles become more prevalent in our everyday lives, we must succumb to the realities of technological deficiencies. Although a future of fully autonomous vehicles would be the pinnacle of safety and efficiency, the current reality leaves us in a transitional state requiring human interaction with autonomous systems. Therefore it is imperative to understand human-system interaction with the autonomous features in current and future technologies. To gain an improved understanding, we designed an investigational study to gain a better understanding of human performance parameters at the moment they relieve and regain control of autonomous systems. The current findings show that reaction time increases as time disengaged from the task of driving increases, regardless of cognitive engagement.